Criminal justice students: A research note - Terry, W. Clinton (American journal of criminal justice, 1984)
During the last five years, there have been a good deal of discussion about the nature, purpose, and future of criminal justice education. On the whole, this research has focused upon three areas of investigation. First, it has focused upon the distribution of criminology and criminal justice programs and majors within the United States. Aside from a few comments about the composition of student bodies as an aspect of the makeup of criminal justice programs (Bennett and Marshall, 1979; Berger, 1980), there is little analysis of criminal justice students. This research note focuses upon an on-going longitudinal research effort which is tracking a cohort of criminal justice majors from their upper level college experience through the first few years of their early career development.